2021
DOI: 10.1186/s12877-021-02462-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of virtual reality exercises on balance and fall in elderly people with fall risk: a randomized controlled trial

Abstract: Background Deficient balance and fear of falling in elderly people can lead to disturbed daily activities, falling, and finally reduced quality of life. Therefore, evaluation of low-risk methods that might partially improve balance in this group of people is of utmost importance. The present study aimed to investigate the impact of Virtual Reality (VR) exercises based on Xbox Kinect on balance and fear of falling among elderly people. Methods This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 42 publications
(56 reference statements)
1
38
0
Order By: Relevance
“…Here, the results of the studies were heterogeneous. Neither Janssen et al (2013) nor Wu et al (2019) found a significant improvement compared to the usual care control group, whereas Cicek et al (2020) and Zahedian-Nasab et al (2021) did. In comparison to conventional exercise, no differences were observed ( Yesilyaprak et al, 2016 ; Cicek et al, 2020 ).…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…Here, the results of the studies were heterogeneous. Neither Janssen et al (2013) nor Wu et al (2019) found a significant improvement compared to the usual care control group, whereas Cicek et al (2020) and Zahedian-Nasab et al (2021) did. In comparison to conventional exercise, no differences were observed ( Yesilyaprak et al, 2016 ; Cicek et al, 2020 ).…”
Section: Resultsmentioning
confidence: 64%
“…From the additional search, another 75 articles were included in the full-text screening, of which 8 met the inclusion criteria. Thus, a total of 28 articles were included in this systematic review ( Chan et al, 2001 ; Brandt and Paniagua, 2011 ; Keogh et al, 2012 ; Pichierri et al, 2012 ; Ulbrecht et al, 2012 ; Janssen et al, 2013 ; Keogh et al, 2014 ; Fu et al, 2015 ; Grigorova-Petrova et al, 2015 ; Rogan et al, 2016 ; Yesilyaprak et al, 2016 ; Delbroek et al, 2017 ; Monteiro-Junior et al, 2017 ; Hutchinson et al, 2018 ; Kamińska et al, 2018 ; Sun et al, 2018 ; Taylor et al, 2018 ; Wu et al, 2019 ; de Bruin et al, 2020 ; Cicek et al, 2020 ; Fakhro et al, 2020 ; Rica et al, 2020 ; Babadi and Daneshmandi, 2021 ; Huang et al, 2021 ; Loggia et al, 2021 ; Marinus et al, 2021 ; Ramnath et al, 2021 ; Zahedian-Nasab et al, 2021 ). The PRISMA flow diagram of the study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations